Trapping by amylose of the aliphatic chain grafted onto chlorogenic acid: Importance of the graft position. (6th March 2015) - Le-Bail, P.; Lorentz, C.; Pencreac'h, G.; Soultani-Vigneron, S.; Pontoire, B.; Giraldo, L.J. López; Villeneuve, P.; Hendrickx, J.; Tran, V.
Highlights: Amylose complexes formation with chlorogenic acid was obtained by hydrothermal method. Lipophilization of chlorogenic acid allowed the formation of amylose complexes. The graft position on the ring of quinic acid has a major importance. Abstract: 5-Caffeoylquinic acid (chlorogenic acid), is classified in acid–phenols family and as polyphenolic compounds it possesses antioxidant activity. The oxydative modification of chlorogenic acid in foods may lead to alteration of their qualities; to counteract these degradation effects, molecular encapsulation was used to protect chlorogenic acid. Amylose can interact strongly with a number of small molecules, including lipids. In order to enable chlorogenic acid complexation by amylose, a C16 aliphatic chain was previously grafted onto the cycle of quinic acid. This work showed that for the two lipophilic derivatives of chlorogenic acid: hexadecyl chlorogenate obtained by alkylation and 3- O -palmitoyl chlorogenic acid obtained by acylation; only the 3- O -palmitoyl chlorogenic acid complexed amylose. The chlorogenic acid derivatives were studied by X-ray diffraction, differential scanning calorimetry and NMR to elucidate the interaction. By comparing the results with previous work on the complexation of amylose by 4- O -palmitoyl chlorogenic acid, the importance of the aliphatic chain position on the cycle of the quinic acid is clearly highlighted. A study in molecular modeling helped to understand the difference in behavior relative to amylose of these three derivatives of chlorogenic acid.